Punica granatum L. protects mice against hexavalent chromium-induced genotoxicity - Renato Ivan de Ávila; Meirielle Teixeira Guerra; Kamilla de Almeida Souza Borges; Marcelo de Sousa Vieira; Luiz Marcos de Oliveira Júnior; Humberto Furtado; Mariana Flavia da Mota; Andréa Fernandes Arruda; Marize Campos Valadares (Universidade de São Paulo, 2013)
This study investigated the chemoprotective effects of Punica granatum L. (Punicaceae) fruits alcoholic extract (PGE) on mice exposed to hexavalent chromium [Cr(VI)]. Animals were pretreated with PGE (25, 50 or 75 mg/kg/day) for 10 days and subsequently exposed to a sub-lethal dose of Cr(VI) (30 mg/kg). The frequency of micronucleated polychromatic erythrocytes in the bone marrow was investigated and the Cr(VI) levels were measured in the kidneys, liver and plasm. For the survival analysis, mice were previously treated with PGE for 10 days and exposed to a single lethal dose of Cr(VI) (50 mg/kg). Exposure to a sub-lethal dose of Cr(VI) induced a significant increase in the frequency of micronucleated cells. However, the prophylactic treatment with PGE led to a reduction of 44.5% (25 mg/kg), 86.3% (50 mg/kg) and 64.2% (75 mg/kg) in the incidence of micronuclei. In addition, the 50 mg/kg dose of PGE produced a higher chemoprotective effect, since the survival rate was 90%, when compared to that of the non-treated group. In these animals, reduced amounts of chromium were detected in the biological materials, in comparison with the other groups. Taken together, the results demonstrated that PGE exerts a protective effect against Cr(VI)-induced genotoxicity.